Use of activated carbon from NiO modified Polyethylene Terephthalate plastic bottle waste to optimize natural gas storage in Adsorbed Natural Gas (ANG) technology - Yuliusman, Yuliusman; Kamilia, Athaya Khanza; Utomo, Anggi Nugroho; Nasruddin, Nasruddin (SINERGI, 2026)
Storage and transportation of natural gas are major challenges in optimizing energy use. To overcome the challenges, Adsorbed Natural Gas (ANG) technology offers a promising alternative for increasing storage capacity at lower pressures. Therefore, this study aims to explore the efficiency of waste polyethylene terephthalate (PET) bottles converted into activated carbon through pre-treatment, carbonization, chemical activation with 4 M KOH, and physical activation using N₂ flow. Modification of activated carbon was carried out using NiO metal impregnation at concentrations of 0.5%, 1%, and 2% to enhance adsorption performance. The results of characterization using iodine number, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) showed that the 2% NiO-impregnated sample had the highest surface area of 997.65 m²/g. Natural gas adsorption and desorption testing showed that this material achieved the maximum storage capacity of 138.9 g/kg at 28°C and 9 bar, with superior performance compared to non-impregnated samples and several previously reported ANG adsorbents. These results showed that combining NiO modification with KOH-activated PET waste improved methane uptake beyond commercial activated carbons and provided an environmentally sustainable solution for plastic waste valorization.